The impact of delayed wound healing on patient-reported outcomes after breast cancer surgery. Issue 11 (November 2022) - Zehnpfennig, Lea; Ritter, Mathilde; Montagna, Giacomo; Handschin, Tristan M; Ling, Barbara M; Oberhauser, Ida; Lévy, Jérémy; Schaefer, Kristin Marit; Maggi, Nadia; Soysal, Savas D; Castrezana López, Liliana; Müller, Madleina M; et al.
Abstract : Purpose: Postoperative complications after breast cancer surgery may be associated with decreased quality of life. It remains unclear whether oncoplastic breast-conserving surgery or mastectomy with reconstruction lead to more postoperative complications than conventional breast surgery (CBS). As delayed wound healing (DWH) is one of the most frequent minor complications, we sought to investigate the significance of DWH for patient-reported outcomes after oncoplastic, reconstructive, and CBS. Methods: Our study is a retrospective cohort study of consecutive patients with stage I-II breast cancer who underwent oncoplastic or CBS performed by three breast surgeons at a single tertiary referral hospital from June 2011 until May 2019. Patient-reported outcomes were evaluated postoperatively using the BREAST-Q questionnaire. Comparisons were made between patients with and without DWH. Results: A total of 229 patients who met the inclusion criteria and 28 (12%) of them developed DWH, 27/158 (17%) in the oncoplastic breast-conserving surgery and reconstruction group and 1/71 (1%) in the CBS group. The mean time from surgery to BREAST-Q assessment was comparable in both groups (29 months in the DWH vs. 33 months in the normal wound healing group). No statistically significant difference for any BREAST-Q scale was detected between patients with and without DWH. This includes physical ( p = 0.183), psychosocial ( p = 0.489), sexual well-being ( p = 0.895), and satisfaction with breasts ( p = 0.068). Conclusion: Our study confirms that oncoplastic breast-conserving surgery and mastectomy with reconstruction lead to significantly more DWH than CBS. However, neither quality of life nor patient-reported outcomes following state-of-the-art reconstructive or oncoplastic breast-conserving surgery at a specialized center seem to be compromised.